Best poems and The book of five makings - Gurney, Ivor 1890-1937 (Mid Northumberland Arts Group u.a., 1995)
Best Poems consists of fair copies Gurney made, with few alterations. The Book of Five Makings is more a working draft, with recastings of the same poems, revealing the process by which he brought his art to completion. Of the 116 poems in this double volume, fewer than a quarter are previously collected. In his introduction R.K.R. Thornton, Professor of English at the University of Birmingham and editor of Gurney's poems and collected letters, sets the books in context. Annotations give readers a clear picture of the books as Gurney wanted them to be